Who is the Troll?: The Construction of Political Identities on Social Media in the Peruvian Context - Cerna-Aragón, Diego Alonso (2017)
One can easily find discrediting accusations between users with different political affiliations or ideological orientations on social media. The objective of this article is to affirm that these practices are neither superfluous nor secondary, but rather fundamental in the formation and consolidation of political identities of those who participate in these discussions. This article reviews up-to-date academic literature about three recent trends in the dynamics of political discussion on social media (the polarization of the political debate, the focus on personalities and figures, and the trolls’ practices) and, using tools taken from Netnography, it explores and applies these concepts to the Peruvian context. Consequently, the article offers an outline about the daily political dynamics on social media, how users take sides and disputes happen, and how this serves to the (re)production of political identities. The results of this investigation show a scenario where two characteristics prevail: the polarization between different political stances and the uncertainty about the information and identities in circulation.